Drivers of beta‐diversity variation in Bromus erectus semi‐natural dry grasslands. Issue 3 (26th December 2012) - Burrascano, Sabina; Anzellotti, Ilaria; Carli, Emanuela; Del Vico, Eva; Facioni, Laura; Pretto, Francesca; Sabatini, Francesco M.; Tilia, Agnese; Blasi, Carlo; Ohlemuller, Ralf
Abstract Questions What are the main drivers of variation in beta‐diversity for Bromus erectus semi‐natural dry grasslands of habitat 6210(*) at different scales? How should environmental variables and spatial patterns be taken into account to conserve the maximum possible beta‐diversity within the habitat? Location Central Italy. Methods We used 195 vegetation relevés distributed in three nested extents: a single mountain, a mountain chain and southern Lazio. Multiple regression on distance matrices was performed using dissimilarity matrices based on: (1) species abundances as response variables; (2) spatial coordinates and environmental parameters (altitude, slope, percentage of rock and stone coverage, aspect, annual rainfall) as explanatory variables. The two groups of explanatory variables were used separately to partition the variation, and jointly to assess the relative contribution of each individual variable. Those variables found to significantly affect beta‐diversity were used to: (1) compare beta‐diversity levels between a set of randomly selected and a set of stratified relevés; and (2) analyse the habitat distribution across environmental gradients. These analyses, together with the curves describing the relationships between spatial distances and composition dissimilarities, were used to inform management decisions for the habitat. Results Most of the variance was explained by environmental variables, whose share was higher in the smallest and intermediate extent than in the broadest extent. Community dissimilarity increased in proportion to differences in altitude and spatial distances at every extent. Accordingly, at all the extents, the selection of relevés stratified by altitude or selected taking into account a minimum spatial distance included significantly higher levels of within‐habitat beta‐diversity, than randomly selected relevés. The relation of beta‐diversity to the variation in aspect and annual rainfall varied at different extents. Conclusions Our results demonstrate that dry grassland management plans aimed at conserving the maximum within‐habitat beta‐diversity should take into account variation in environmental variables, among which altitude proved to be a critical factor at every extent. Also, spatial distances positively affect within‐habitat beta‐diversity levels, and scale‐dependent minimum distances among habitat patches should be taken into account when selecting patches of habitat 6210(*) to be conserved in the study area.